WHITE’S CULTURAL INVASION THROUGH BEAUTY MYTH IN TONI MORRISON’S THE BLUEST EYE - -, SULISTYANINGRUM (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: cultural invasion, beauty myth, African-American, Toni Morrison, TheBluest Eye Cultural invasion aims to brainwash marginalized group to make them follow the culture of the invader. It influences each component of way of life, including the way women build a concept of beauty. In fact, the concept of beauty is influenced by the White as a dominant group. The Bluest Eye novel by Toni Morrison explores Pecola Breedlove, a victimized African-American girl of White beauty standard. Therefore, the study conducted investigates on how the era of 1940s, as the setting of time of the novel, shapes the beauty standard and how the images of beauty are constructed through culture. In addition, this study observes on what are the impacts of beauty myth to Pecola Breedlove. Socio-cultural approach is used in this study since it deals with one’s relation with society and its culture. This approach leads to the use of cultural invasion’s theory to analyse sociological condition when the inferior culture is invaded by the superior one. Whereas, theories of ideology, power, and hegemony are applied to analyse capitalism issue. The last, to discover Pecola Breedlove’s perspective of ideal beauty, the concept of beauty myth purposed by Naomi Wolf is used. The result of this research shows that through four kinds of cultural commodities, girl’s dolls, girl favourite stars, mass media, and movie stars, the beauty myth are infused to change the African-American’s perspective of beauty. Succeedingly, cultural invasion gives two impacts to Pecola Breedlove, adoration to the White beauty standard and obsession to have blue eyes.The following researcher is suggested to explore another significant character, Claudia Macteer, especially on her resistance against White beauty myth by using Black feminism theory. Furthermore, archetypal literary criticism, specifically the using of seasons in Northrop Frye’s archetypal schema is applicable since Claudia’s life moves through a cycle of four seasons—autumn, winter, spring, and summer.